2021
DOI: 10.4269/ajtmh.20-0773
|View full text |Cite
|
Sign up to set email alerts
|

Lassa Fever among Children in Eastern Province, Sierra Leone: A 7-year Retrospective Analysis (2012–2018)

Abstract: Pediatric Lassa fever (LF) usually presents as a nonspecific febrile illness, similar to other endemic diseases in countries like Sierra Leone, where LF is considered to be hyperendemic. The nonspecificity of presentation and lack of research have made it difficult to fully understand best practices for pediatric management. We aim to describe clinical characteristics of hospitalized pediatric patients suspected or diagnosed with LF and assess factors associated with hospital outcomes among those with LF antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…More recently, CFRs for LF have reached 69% in Sierra Leone and may exceed 80% in third-trimester pregnancies [18,20,21]. Other recent studies in Sierra Leone revealed LF CFRs of 67% in hospitalized patients and 63% in hospitalized children [22,23]. Countries reporting LF outside of Sierra Leone have historically reported lower CFRs.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, CFRs for LF have reached 69% in Sierra Leone and may exceed 80% in third-trimester pregnancies [18,20,21]. Other recent studies in Sierra Leone revealed LF CFRs of 67% in hospitalized patients and 63% in hospitalized children [22,23]. Countries reporting LF outside of Sierra Leone have historically reported lower CFRs.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted at KGH, in Kenema District of Eastern Province, Sierra Leone. KGH has a catchment area endemic for illnesses such as malaria and Lassa fever (LF) and is a hospital that was at the epicenter of Sierra Leone´s efforts during the 2014–2016 West African Ebola outbreak [ 19 , 23 , 24 ]. The pediatric ward of KGH provides free health care for children under five years of age and admits approximately 400 children per month.…”
Section: Methodsmentioning
confidence: 99%
“…KGH, located in Kenema District of Eastern Province, has a catchment area of roughly 600,000 persons and was at the epicenter of Sierra Leone’s efforts during the 2014–2016 West African Ebola outbreak [ 31 , 33 ]. The pediatric ward admits ~ 400 children per month.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, Sierra Leone is still one of the countries with the highest under-five mortality rates. In order to address this, the “Free Health Care Initiative” was implemented in 2010, establishing free health services to pregnant women, lactating mothers, and children under-five throughout the country [ 20 , 31 ].…”
Section: Introductionmentioning
confidence: 99%